2023
DOI: 10.1088/1361-6382/acbadc
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the far-field phase and the tilt-to-length error contribution in space-based laser interferometry

Abstract: The arm length of the space-based interferometer for gravitational wave detection is 108~109 m, and picometer precision is required. The wavefront error in the far-field coupled with the pointing jitter is a major noise source, which raises higher requirements of the wavefront quality of the telescope. By extending the analytical solutions of the far-field phase to 21 Zernike aberrations, this paper demonstrates that the far-field phase could be regarded as the sum of the effects of the individual aberrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The optical system design was carried out with the goal of achieving a wavefront error RMS < λ/250 at the telescope exit pupil [19][20][21]. The final design resulted in a wavefront error RMS value of 0.0035λ at the telescope exit pupil, as shown in figure 9 (left), meeting the target requirement.…”
Section: Design Results With Rms Value Of Wavefront Error As the Opti...mentioning
confidence: 99%
See 2 more Smart Citations
“…The optical system design was carried out with the goal of achieving a wavefront error RMS < λ/250 at the telescope exit pupil [19][20][21]. The final design resulted in a wavefront error RMS value of 0.0035λ at the telescope exit pupil, as shown in figure 9 (left), meeting the target requirement.…”
Section: Design Results With Rms Value Of Wavefront Error As the Opti...mentioning
confidence: 99%
“…Moreover, the Tianqin gravitational wave detector is an aperture conjugate system, effectively suppressing the diffraction effect. Therefore, the flat-top beam received by the receiving end telescope and transmitted through the telescope system to the detector can be represented as a flat-top beam [17][18][19] with wavefront aberration W(ρ,θ), where: (ρ,θ) .…”
Section: Calculation Model For Ttl Coupling Noise Inside the Telescopementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that the wavefront of an emitted beam is not ideally spherical but distorted in reality, which leads to additional phase noise at the receiving satellite when combined with pointing jitters of the emitting beam (see, e.g. [17,[21][22][23][24]). Various factors including aberration in the optical system contribute to this phase deviation which is denoted by w e (x, y, z).…”
Section: Effect Of Far-field Wavefront Errormentioning
confidence: 99%
“…The z 0 is the piston term, which is omitted because it does not cause any changes in the TTL-coupling noise. The z 1 = 2ρ cos θ represents the tilt term in the x-direction, and z 2 = 2ρ sin θ represents the tilt term in the y-direction [14]. By combining the tilt terms in equation ( 6), the wavefront aberration at the exit pupil of the telescope for any pointing deviation angle α can be expressed as:…”
Section: Wavefront Distortion and Pointing Jitter Coupling Noisementioning
confidence: 99%